1997
DOI: 10.1159/000291402
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms in Vaginal Fluid from Women in Prolonged Pregnancy

Abstract: In order to compare the vaginal microflora of women in prolonged pregnancy with that of women who delivered at term, samples for quantitative aerobic and anaerobic microbiological culture were collected from 100 women at 42 weeks of gestation and from 60 women at term. The occurrence of lactobacilli-dominated flora was similar in women at term and women with prolonged pregnancy. However, non-hydrogen-peroxide-producing lactobacilli (p < 0.01) were significantly more common and Peptostreptococci species (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Increased risk of maternal colonization with longer duration of gestation may be due to the disruption of the vaginal ecosystem in extended pregnancy, which leads to an increase in non-hydrogen-peroxide-producing lactobacilli (Goffeng et al, 1997). Women with increased nonhydrogen-peroxide-producing lactobacilli are more likely to have bacterial vaginosis and symptomatic vaginal candidiasis (Hillier, Krohn, Klebanoff, & Eschenback, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased risk of maternal colonization with longer duration of gestation may be due to the disruption of the vaginal ecosystem in extended pregnancy, which leads to an increase in non-hydrogen-peroxide-producing lactobacilli (Goffeng et al, 1997). Women with increased nonhydrogen-peroxide-producing lactobacilli are more likely to have bacterial vaginosis and symptomatic vaginal candidiasis (Hillier, Krohn, Klebanoff, & Eschenback, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…We defined mammary candidosis as a positive culture plus at least one of the following five symptoms: burning nipples, painful breasts, stabbing pain throughout the breast, shiny skin on the nipple/areola area, or flaky skin on the nipple/areola area. These symptoms were chosen because they are the most commonly reported symptoms attributed to breast yeast infections in the literature (Geiger et al, 1995;Goffeng, Holst, Nilsson, Milsom, & Andersch, 1997;MacDonald, 1995). Of the 23 women in the SG who cultured positive at 2 weeks postpartum, 20 (87%) developed symptoms and were considered clinically positive for mammary candidosis between 2 and 9 weeks postpartum, whereas only 16% (12/77) of those who cultured negative had at least one of the five symptoms listed above (χ 2 = 41.5, p < .0001).…”
Section: Rates Of Colonization Candidosis and Infant Thrushmentioning
confidence: 99%
“…In a study of 7918 pregnant women, Hillier et al found that VVC was associated either with normal vaginal microbiota (dominated by lactobacilli) or with intermediate flora (with decreased lactobacilli). 12 Some other studies suggested that pregnant 13,14 or post-term 15 women whose vaginas were colonized by H 2 O 2 -producing lactobacilli were less likely to have symptomatic VVC than those colonized with H 2 O 2 -nonproducing vaginal lactobacilli. However, Hawes et al 16 suggested that H 2 O 2 -producing lactobacilli do not protect against VVC.…”
Section: Vaginal Lactobacilli and Pathogenesis Of Vvcmentioning
confidence: 99%
“…All women were consecutively enrolled from prior studies [4,[21][22][23]. In total, 312 samples for fetal fibronectin measurement and microbiological culture were obtained.…”
Section: Study Populationmentioning
confidence: 99%